Three-dimensional printed poly (L-lactide) and hydroxyapatite composite for reconstruction of critical bone defect in rabbits - Minto, Bruno Watanabe [UNESP]; Sprada, Aricia Gomes [UNESP]; Goncalves Neto, Jose Aloizio [UNESP]; Alcantara, Brenda Mendonca de [UNESP]; Sa Rocha, Thiago Andre Salvitti de [UNESP]; Valentim Hespanha, Ana Carolina [UNESP]; Quarterone, Carolina [UNESP]; Sartori, Maressa da Rocha [UNESP]; Hataka, Alessandre [UNESP]; Ramirez Uscategui, Ricardo Andres [UNESP]; Gosuen Goncalves Dias, Luis Gustavo [UNESP] (Acta Cirurgica Brasileira, 2021)
Purpose: To use a 3D printed poly (L-lactide) acid (PLLA) and hydroxyapatite (HA) composite as a bone substitute for reconstruction of a critical bone defect in the radius of rabbits. Methods: A 1.5 cm ostectomy was performed in the radial diaphysis of 60 New Zealand white rabbits. The rabbits were divided into three groups according to surgical treatment of the bone defect (group I - control, group II - bone graft, group III - 3D PLLA). Each group was divided into four subgroups with different radiographic and histopathologic evaluation times (T1 - 15 days, T2 - 30 days, T3 - 60 days, T4 - 90 days). Results: The implant group had greater clinically lameness (p = 0.02), edema (p = 0.007), pain (p = 0.04) and more complications at the surgical site (p = 0.03). Histologically, this group showed greater congestion (p = 0.04), hemorrhage (p = 0.04) and inflammation. Osteogenesis was microscopically similar between days (p = 0.54) and treatments (p = 0.17), even though radiographically, more effective bone healing occurred in the graft group (II), with more callus and bone bridge formation. Conclusions: The customization of a 3D PLLA/HA scaffold was successful. However, in animals receiving the polymer-ceramic composite less bone callus and bone bridge was formed compared to the graft group.
Keywords: Biocompatible Materials; Osteogenesis; Tissue Scaffolds; Tissue Engineering; Rabbits